A rare cause of acute abdomen in postmenopausal women: borderline mucinous ovarian tumor with torsion - Singhal, Tanya; Marandi, Satyabhama; Sahu, Sugatha; Pattayat, Keshari Rajmohan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Ovarian torsion accounts for 2–3% of gynecological emergencies and is typically associated with benign, mobile ovarian cysts in reproductive-age women. Torsion involving malignant or borderline ovarian tumors is rare, particularly in postmenopausal women, and may obscure timely diagnosis and management. We report a rare case of a 45-year-old postmenopausal woman presenting with acute abdominal pain, nausea, and vomiting. Clinical examination revealed a large, firm abdominopelvic mass with restricted mobility. Ultrasound and contrast-enhanced CT demonstrated a 20 cm multiloculated right ovarian mass with solid components and >270° vascular pedicle torsion, raising suspicion for malignancy. Tumor markers showed normal CA-125 and CEA but elevated CA-19.9. The patient underwent staging laparotomy with total abdominal hysterectomy, bilateral salpingo-oophorectomy, and omentectomy. Intraoperatively, a 20 cm twisted ovarian mass with areas of hemorrhage and necrosis was identified. Histopathology confirmed a mucinous borderline ovarian tumor with microinvasion, confined to the right ovary (FIGO stage pT1a). The contralateral ovary unexpectedly showed a benign Brenner tumor. Omentum and peritoneal cytology showed no malignant involvement. This case underscores that adnexal torsion in postmenopausal women warrants a high index of suspicion for malignancy. Mucinous tumours may present with normal CA-125 but elevated CA-19.9, particularly in the setting of torsion. Early imaging, comprehensive evaluation, and prompt surgical staging are crucial to prevent complications such as capsular rupture and peritoneal dissemination. Timely management in this case enabled complete oncologic surgery and a favorable postoperative outcome.